Compositional nonuniformities in pulsed laser atom probe tomography analysis of compound semiconductors - Mueller, M; Smith, G; Gault, B; Grovenor, C (2012)
The unidirectional laser illumination of atom probe tomography specimens can result in changes of the apex morphology from nearly hemispherical to asymmetrical with different local radii of curvature, implying an anisotropic field distribution across the sample surface. In the analysis of III-V semiconductors, this affects the process of field dissociation of group-V cluster ions and introduces variations in the apparent composition across the field of view. We have studied this phenomenon in GaSb and propose an explanation for these compositional variations in terms of the locally varying extent of field dissociation of group-V cluster ions and ion pile-up effects on the detector. The optimization of experimental conditions and possible modifications to the instrument design are discussed to mitigate the compositional variations. © 2012 American Institute of Physics.